Halangan Dalam Penggunaan Peralatan Teknologi Dalam Pengajaran Bahasa Arab Kepada Bukan Penutur Jati : Kajian di USIM, UIAM dan UKM - Lubna Abd. Rahman (Universiti Sains Islam Malaysia, 2024)
It is undeniable that the use of ICT tools such as audio visual materials contributes a lot towards the smooth-running of the language teaching and learning process especially foreign languages such as Arabic. Furthermore, it helps instructors (teachers and lecturers) to manage their time while teaching the subjects. From the observation, it is found that some of the Arabic instructors prefer to apply the traditional method of teaching such as talk and chalk, rather than using any audio visual materials as their method of teaching, particularly in teaching language skills such as reading and writing. This may due to some obstacles and problems while using the ICT tools as their educational aids. It may also due to problems related to the curriculum, the instructors themselves, or their institutions. Thus, this study determines to find out the factors that hinder the instructors from using the tools widely and regularly in the teaching of Arabic for the non-native speakers. To achieve this, questionnaires and interviews were carried out to selected universities namely Islamic Sciences University of Malaysia (USIM), International Islamic University Malaysia (IIUM) and Universiti Kebangsaan Malaysia (UKM) to identify the obstacles and problems encountered by the respondents.